Dark regards - Hill, Dave, 1974- (Oni Press, 2026)
Two decades ago, Dave Hill and his first band set out to rock their high school auditorium in a fury of heavy metal hellfire. They failed miserably. Years later, Dave has made a new life for himself as a rising star in the New York comedy scene--a career where getting laughed at on stage is the entire point and not just a tragic consequence. But when Dave's metal ambitions are reawakened by the über self-serious "satanic" genre of Norwegian black metal, Dave creates a ridiculously hyperbolic alter ego and a band to match that, together, reignite the spark of his forgotten rock 'n' roll fantasy. But when Dave's internet-fueled rumors of Witch Taint--a metal band "so extreme that you must remove all sharp objects from the immediate area" when their music is played--spreads all the way to Europe, his story will spiral dangerously out of control as Norway's most extreme black metal butchers come to reap their revenge . . .